Development of Environment-Based Comic Learning Media for Junior High School Class VIII (Universitas Negeri Semarang, 2022)
Based on interviews that have been conducted by researchers with teachers and also the school. The results of field observations obtained data that so far the learning media used is still fixated with printed books in schools. The media used only uses learning media such as power points. This research used the Research and Development (R&D) method of the ADDIE model. The data source is obtained from primary data and secondary data. The subjects in this study were students of SMP Negeri 1 Seponti Jaya VIII IPS for the 2022/2023 academic year which consisted of two classes, namely class VIII. The data collection techniques used in this study used observation and questionnaire methods. Meanwhile, the data analysis technique used in this study is qualitative analysis using walkthrough techniques. Based on the results of the research and discussion, the following conclusions were obtained: (1) This development research uses the concept of the ADDIE development model. Model development consists of five stages, namely: Analysis, Design (desing), Development (Development), Implementation (Implementation), Evaluation (evaluation), (2) Environmental-based digital comics are declared valid with validity according to validators of 85.3 with very valid categories, and (3) Environmental-based digital comics are declared effective according to the results of the N-Gain calculation which shows that the N-Gain score of 0.31 is included in the category of quite effective.